Drug-resistant bacteria screening and patient barrier precautions are associated with decreased neonatal nosocomial infection - Li-rong Guan; Jia Chen; Li-rong Wei; Xiao-shuang Wang; Dan Xue; Qin-yu Yang; Yan-ping Li; Jing Yu (Journal of Infection in Developing Countries)
Introduction: Neonates are at high risk of nosocomial infections, especially in developing countries. This study aimed to examine the effectiveness of drug-resistant bacteria (DRB) screening in combination with patient barrier precautions in controlling nosocomial infections in neonatal wards.